I-mode studies at ASDEX Upgrade: L-I and I-H transitions, pedestal and confinement properties. (28th September 2016) - Ryter, F.; Fischer, R.; Fuchs, J.C.; Happel, T.; McDermott, R.M.; Viezzer, E.; Wolfrum, E.; Barrera Orte, L.; Bernert, M.; Burckhart, A.; da Graça, S.; Kurzan, B.; et al.
Abstract: The I-mode is a plasma regime obtained when the usual L-H power threshold is high, e.g. with unfavourable ion ∇ B direction. It is characterised by the development of a temperature pedestal while the density remains roughly as in the L-mode. This leads to a confinement improvement above the L-mode level which can sometimes reach H-mode values. This regime, already obtained in the ASDEX Upgrade tokamak about two decades ago, has been studied again since 2009 taking advantage of the development of new diagnostics and heating possibilities. The I-mode in ASDEX Upgrade has been achieved with different heating methods such as NBI, ECRH and ICRF. The I-mode properties, power threshold, pedestal characteristics and confinement, are independent of the heating method. The power required at the L-I transition exhibits an offset linear density dependence but, in contrast to the L-H threshold, depends weakly on the magnetic field. The L-I transition seems to be mainly determined by the edge pressure gradient and the comparison between ECRH and NBI induced L-I transitions suggests that the ion channel plays a key role. The I-mode often evolves gradually over a few confinement times until the transition to H-mode which offers a very interesting situation to study the transport reduction and its link with the pedestal formation. Exploratory discharges in which n = 2 magnetic perturbations have been applied indicate that these can lead to an increase of the I-mode power threshold by flattening the edge pressure at fixed heating input power: more heating power is necessary to restore the required edge pressure gradient. Finally, the confinement properties of the I-mode are discussed in detail.